Investigating the Effect of Yeasts and their Derivatives on the Qualitative Indices of Red Wine - Kazumyan, K. N.; Mikaelyan, M. N.; Gevorgyan, E. R.; Jraghatspanyan, A. A. (ՀԱԱՀ հիմնադրամ)
The study on the influence of yeast and yeast derivative autolyzes on the wine qualitative and quantitative characteristics has been conducted upon the first article of the series. Red grapes contain more than 1500 components, which are forming the taste and aroma of red wines, as well as the biological value of the product. One of the main technological operations in the production of red wines, which is related to the creation of favorable conditions for extracting phenolic and coloring compounds from the solid parts of the grape berry that are responsible for the color, taste, and aroma preserving them at the different stages of the wine formation and maturation, has been researched and analyzed.
Keywords: Food Science and Technology